Infiltrative and drug‐resistant slow‐cycling cells support metabolic heterogeneity in glioblastoma. (15th October 2018) - Hoang‐Minh, Lan B; Siebzehnrubl, Florian A; Yang, Changlin; Suzuki‐Hatano, Silveli; Dajac, Kyle; Loche, Tyler; Andrews, Nicholas; Schmoll Massari, Michael; Patel, Jaimin; Amin, Krisha; Vuong, Alvin; Jimenez‐Pascual, Ana; et al.
Abstract: Metabolic reprogramming has been described in rapidly growing tumors, which are thought to mostly contain fast‐cycling cells (FCCs) that have impaired mitochondrial function and rely on aerobic glycolysis. Here, we characterize the metabolic landscape of glioblastoma (GBM) and explore metabolic specificities as targetable vulnerabilities. Our studies highlight the metabolic heterogeneity in GBM, in which FCCs harness aerobic glycolysis, and slow‐cycling cells (SCCs) preferentially utilize mitochondrial oxidative phosphorylation for their functions. SCCs display enhanced invasion and chemoresistance, suggesting their important role in tumor recurrence. SCCs also demonstrate increased lipid contents that are specifically metabolized under glucose‐deprived conditions. Fatty acid transport in SCCs is targetable by pharmacological inhibition or genomic deletion of FABP7, both of which sensitize SCCs to metabolic stress. Furthermore, FABP7 inhibition, whether alone or in combination with glycolysis inhibition, leads to overall increased survival. Our studies reveal the existence of GBM cell subpopulations with distinct metabolic requirements and suggest that FABP7 is central to lipid metabolism in SCCs and that targeting FABP7‐related metabolic pathways is a viable therapeutic strategy. Synopsis: Transcriptomic and metabolomic profiling of primary brain tumor cells demonstrate that functionally different glioblastoma (GBM) cell subpopulations depend on distinct metabolic pathways for their growth and survival. More invasive slow cycling tumor cells rely on oxidative phosphorylation and lipid metabolism, suggesting targetable candidates for the inhibition of treatment‐resistant tumors. Patient‐derived GBM cells contain fast‐cycling cells (FCCs) relying on aerobic glycolysis and slow‐cycling cells (SCCs) depending on mitochondrial oxidative phosphorylation in vivo . SCCs show increased resistance, invasion, and metabolic gene signatures characteristic of recurrent tumors. SCCs show increased levels of metabolites and components involved in lipid metabolism, storage, and transport. Block of FABP7‐dependent exogenous fatty acid uptake decreases resistance of SCCs to chemotherapy and glucose deprivation. Abstract : Oxidative phosphorylation and lipid metabolism specify distinct energetic set‐up of invasive brain tumor cells.